An evaluation of the Holy Family School High School Library's reference collections and services - Ubana, Rhea Rowena M. (Institute of Library Science, University of the Philippines Diliman, 2001)
This study aimed to evaluate the adequacy of the reference collections and sufficiency of the reference services of the Holy Family School (HFS) High School Library in meeting the academic needs of the high school students in each level. It also aims to find out the problems encountered by the students in using the reference collections and services, thereby suggesting solutions for further improvements. Both quantitative and the qualitative methods of evaluation were used. The quantitative methods used were: the absolute size of the reference collections; the growth rate, and; the examination of the number of collections against the minimum standards set by PAASCU and DECS for secondary school libraries. For the qualitative method, the impressionistic approach was used, utilizing survey questionnaires, and observing students' pattern of using the reference collections.